Factor analysis of medical image sequences in MR of head and neck tumors. - Zagdanski, A M; Sigal, R; Bosq, J; Bazin, J P; Vanel, D; Di Paola, R (American Journal of Neuroradiology, 1994)
PURPOSE To evaluate factor analysis of medical image sequences (FAMIS), a means whereby physiologic contrast enhancement kinetics, called factors, and their spatial distribution, termed factor images, are estimated after acquisition of dynamic MR images. The method is intended to recognize and characterize the different tissue kinetics automatically. METHODS This method was evaluated in a series of 22 patients with head and neck tumors. Eleven patients presented with a previously untreated lesion. Six were examined for tumor recurrence, previously treated by multiple therapies. Five patients had preoperative chemotherapy and underwent MR before and after chemotherapy. In all cases, MR images were correlated with surgical and pathologic data. MR examinations were performed on a 1.5-T unit with static sequences and dynamic sequences acquired after bolus injection of gadolinium and processed by FAMIS. RESULTS FAMIS was able to identify three factors representing contrast-enhancement kinetics and their associated factor images. The neoplastic component was associated with the earlier factor image, F1. Fibrosis and chemotherapy and/or radiation-induced changes were associated with the two later factors, F2 and F3. The limits of this method were highly vascularized tissues whose earlier factor was similar to that of neoplastic tissues (mucosae and salivary glands), patient motion, responsible for artifacts in FAMIS, and lesions of less than 5 mm. CONCLUSION FAMIS of dynamic MR studies was useful for differentiating neoplastic tissue from tissue having undergone changes by chemotherapy and/or radiotherapy, but it did not improve the ability of MR to characterize neoplastic tissues in previously untreated patients.